2017
DOI: 10.4102/rw.v8i1.141
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of teachers on creating space for code switching as a teaching strategy in second language teaching in the Eastern Cape province, South Africa

Abstract: This research reports on the findings regarding the perceptions of teachers towards creating space for the use of code switching as a teaching strategy in Afrikaans learning and teaching in the isiXhosa-speaking environments of the Transkei region. The aim of this investigation was to establish whether or not code switching can be used as a teaching strategy. A sample of 13 teachers from 12 schools was purposefully selected. A qualitative approach was used. Interviews and semi-structured questionnaires were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Although the teachers in this research claimed that they used CS unconsciously -CS came naturally -the teachers were aware that CS that they did have certain functions that could help their students learn L2 effectively and efficiently. Another study by Songxaba, Coetzer, and Molepo (2017) which investigated the teachers' perception on the use of CS as a strategy in second language teaching in Afrika. This study also revealed that teachers also hold positive perception about the use of CS in this study.…”
Section: Teachers' Perception Toward the Use Of Cs In Esl Classroomsmentioning
confidence: 99%
“…Although the teachers in this research claimed that they used CS unconsciously -CS came naturally -the teachers were aware that CS that they did have certain functions that could help their students learn L2 effectively and efficiently. Another study by Songxaba, Coetzer, and Molepo (2017) which investigated the teachers' perception on the use of CS as a strategy in second language teaching in Afrika. This study also revealed that teachers also hold positive perception about the use of CS in this study.…”
Section: Teachers' Perception Toward the Use Of Cs In Esl Classroomsmentioning
confidence: 99%
“…Additionally, experienced EFL teachers used codeswitching more frequently than novice teachers. This result is supported by Puspawati (2018), Bilgin (2016), and Songxaba, Coetzer and Molepo (2017). English in Chinese-dominated classrooms comes from textual materials.…”
Section: Discussionmentioning
confidence: 75%
“…Bilgin (2016) also mentioned that the use of codeswitching is related to teachers' teaching experience, and experienced teachers in Turkey took advantage of codeswitching to explain language points. Songxaba, Coetzer, and Molepo (2017) supported this viewpoint and pointed out experience teachers could create space for using codeswitching as a teaching strategy in Afrikaans learning and teaching.…”
Section: Literature Reviewmentioning
confidence: 83%
“…Then and Ting (2009) declared that in circumstances where studentsí proficiency in the instructional language is not sufficient enough, code-switching would be a necessary tool for teachers to get their messages across effectively to the students. Songxaba (2017) reported a gradual move from a high tolerance of code-switching in lower levels to a low tolerance of code-switching in higher levels.…”
Section: Related Studies On Code-switchingmentioning
confidence: 98%